KONSPIRASI MEDIA MASSA DAN PENGEMBALIAN BAHASA PADA HAKIKATNYA:: SEBUAH PENERAPAN METODE ANALISIS TINDAK TUTUR KOMUNIKASI - Wahyu Wibowo (Sekolah Tinggi Agama Islam Sadra, 2014)
The twenty-first century may be referred to as the century of language, considering how human life is inseparable from the various forms of mass media. However, concerning the construction of facts and reality, especially whenever mass-media becomes colored by ego-centric tendencies, biases in reporting frequently occur that raiseethical problems. It follows that there has been a conspiracy behind mass-mediathat has impact inobstructing the function of media as a forum for political education for the people. Therefore, in order to reveal the conspiracy a new media text analysis method –which in this paper is called speech-act analysis method of communication– is required. The method is heuristically, critically and contextually brought about through contemporary principles of Ordinary Language Philosophy. Thereby, in addition asserting that mass communication should be used ethically and with emancipation, this method will also examine the other media text analysismethods which have been known but may not be useful to discover conspiracy behind mass-media reports.